Retention of polyurethane foam fragments during VAC therapy: a complication to be considered. Issue 2 (17th April 2013) - Dessy, Luca A; Serratore, Francesco; Corrias, Federico; Parisi, Paola; Mazzocchi, Marco; Carlesimo, Bruno
Abstract: Vacuum‐assisted closure (VAC) therapy is a closed‐loop, non‐invasive active system, characterised by a controlled and localised negative pressure applied on porous polyurethane absorbent foams. It promotes healing of acute and chronic wounds. Therapeutic effects of VAC therapy have been proved and demonstrated; however, this method can have some disadvantages. Even if it is a quite versatile device, only qualified medical/paramedical personnel should use it in order to avoid possible complications that can occur after an improper application. In this report, 11 cases of foam‐fragment retention within the wound are presented. This rare complication did not promote healing, but further hindered it. On the basis of our experience, it is mandatory to define the indications, benefits and limitations of VAC therapy.